ECONOMIC ADAPTATION OF THE NEW NORMAL COMMUNITY DURING COVID-19 PANDEMIC: CASE STUDY OF SONGKHLA, PHATTHALUNG AND SATUN PROVINCES. - Chaisri, Saifon (Academic Journal Phranakhon Rajabhat University, 2021)
This study aimed to study the impact on living and economic adaptation during Covid-19 pandemic to New Normal community in Songkhla, Patthalung, and Satun provinces. The samples were collected form 400 households of each province, so there were 1,200 households in total. The findings revealed that the Covid-19 pandemic affected their living and adaptation at a moderate level. For the economic impact, decline in income (65.25%), in saving money (54.17%) and in purchasing power (44.75%) were found. Regarding unemployed status, permanently laid off (8.08%), reduced working day and hours (7.25%) and temporarily laid off (6%) were discovered. There were economic concerns about the higher cost of living (30.94%), no earned or reduced income and possible debt (27.70%). For economic adaptation, there was no new occupation to compensate their lost income (88.40%) but they developed the essential skill for future work (43.41%) and changed their purchasing behavior (44.75%). The new normal of economic revealed that there was saving money as emergency budget (77.62%), technological application to work (75.97%), career and financial planning for the future (74.33%), adopting the principles of sufficiency economy (72.12%), increasing opportunities to earn more income by doing additional occupations such as food delivery, online selling (65.21%) and self-development for new skills, reskills and upskills in order to prepare for career changes (62.66%) respectively.